2009
DOI: 10.1590/s0365-05962009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Inclusões de quitosana no subcutâneo de rato: avaliação clínica, histológica e morfométrica

Abstract: FUNDAMENTOS: A quitosana é polímero derivado da quitina, com vários tipos de aplicação na área médica. OBJETIVO: Avaliar a biocompatibilidade de membranas de quitosana no subcutâneo de ratos. MÉTODOS: Foram utilizados 20 ratos "Wistar" machos, nos quais foram implantadas membranas de quitosana, na região mediana dorsal. Os animais foram sacrificados: sete, 15, 30 e 60 dias após a cirurgia, tendo sido avaliados clinicamente durante o período experimental e com fotodocumentação no momento do sacrifício. Após o s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
2
8
0
4
Order By: Relevance
“…The authors verified that the presence of nanostructured chitosan favored the cell proliferation, imitating the extracellular matrix properly. These results are similar to those found by Brito et al 23 using collagen and chitosan nanostructured membranes as a growth matrix for human fibroblasts verifying the non-toxic characteristic for cells. The authors of that study also used the composites in animals to verify the effectiveness on skin healing, and concluded that the composite showed better results when compared to commercially available collagen membranes.…”
Section: In Vitro Biocompatibility Evaluationsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors verified that the presence of nanostructured chitosan favored the cell proliferation, imitating the extracellular matrix properly. These results are similar to those found by Brito et al 23 using collagen and chitosan nanostructured membranes as a growth matrix for human fibroblasts verifying the non-toxic characteristic for cells. The authors of that study also used the composites in animals to verify the effectiveness on skin healing, and concluded that the composite showed better results when compared to commercially available collagen membranes.…”
Section: In Vitro Biocompatibility Evaluationsupporting
confidence: 91%
“…Oliveira et al (2008) 22 submitted chitosan samples in diverse concentrations to in vitro cytotoxicity tests and confirmed that changes in chitosan concentrations did not affect the non-toxic characteristic of the material, however, pH variations of the formulations caused cell lysis. Brito et al (2009) 23 implanted chitosan membranes in the subcutaneous of rats for biocompatibility evaluation and observed a little inflammatory reaction with fibrosis formation (pseudocapsule) around the samples. The authors stated that the characteristics observed allow to consider that the material can be used for tissue repair.…”
Section: In Vitro Biocompatibility Evaluationmentioning
confidence: 99%
“…In addition, there was considerable decrease in the amount of material and even complete degradation. Brito et al (2009), in a similar study, also had trouble finding the site of the procedure due to the degradation of the material, after the same period of implantation. That is due to the fact that chitosan is fragmented by enzymatic action, as well as the lysozyme, when contacting the animal tissues (Laranjeira and Fávere, 2009).…”
Section: Resultsmentioning
confidence: 82%
“…Separate simple suture was applied by using a 2-0 polyamide thread. The antibiotic therapy was based on 10% enrofloxacin intraperitoneally, in addition to the topic application of 2%-mupirocin-based ointment (Brito et al, 2009). For analgesia, a 0.2 mg/kg dose of butorphanol was administered subcutaneously during two days (Massone, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Esses dados diferem de outros estudos feitos pelo mesmo grupo de pesquisadores que desenvolveram o presente estudo,quando foram avaliados coelhos com cavidade anoftálmica que receberam implantes debiovidro e biovidrocerâmico, que apresentaram edema e elevada infiltração de neutrófilos no início do período de experimentação (21) ou em ratos que receberam implantes de quitosana no subcutâneo, os quais apresentaram elevada resposta inflamatória nos primeiros 15 dias após o implante, notadamente com presença de linfócitos e neutrófilos (22) .…”
Section: Tabelaunclassified